To prove this identity, we can start by expending the left side:
![(x+y)^3=(x+y)(x+y)(x+y)](https://img.qammunity.org/2023/formulas/mathematics/college/7xbv792wqsji09fx70pdx6uu598agez75x.png)
Now, we can apply the distributive property in two of these factors:
![(x+y)(x+y)=x\cdot x+x\cdot y+y\cdot x+y\cdot y=x^2+xy+xy+y^2=x^2+2xy+y^2](https://img.qammunity.org/2023/formulas/mathematics/college/99v7zf9ymv8kw4jx4qp3mnl8na72j96yuu.png)
Now, we substitute it back:
![(x+y)^3=(x+y)(x^2+2xy+y^2)](https://img.qammunity.org/2023/formulas/mathematics/college/i3g6sq10zyibp43exm6bhnlj8y6h1isdx4.png)
And now, we can apply the distributive property again:
![\begin{gathered} (x+y)(x^2+2xy+y^2)=x\cdot x^2+x\cdot2xy+x\cdot y^2+y\cdot x^2_{}+y\cdot2xy+y\cdot y^2= \\ =x^3+2x^2y+xy^2+x^2y+2xy^2+y^3=x^3+3x^2y+3xy^2+y^3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rkcvv37zvhs5wyrc8jx1g54unupdjs1jn7.png)
Going back to the equation, we have:
![(x+y)^3=x^3+3x^2y+3xy^2+y^3](https://img.qammunity.org/2023/formulas/mathematics/college/nyfhtwh17rm6csy2rktqxxrogp65mr8e8d.png)
The two middle terms have the factors "3", "x" and "y" in common, so we can factor them out:
![\begin{gathered} (x+y)^3=x^3+3xy(x+y)+y^3 \\ (x+y)^3=x^3+y^3+3xy\mleft(x+y\mright) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2ciiqsg3swsjyhmbeva32usy0qq7wladb7.png)
And we end up with the identity we wantd to prove, so it is proved.